Grand Design Of The Organizational Identity Of The Uin Jakarta Career Center: Dynamics Of Career Welfare And Career Adaptability To The Perception Of Graduate Career Feasibility - Nasichah; Abdul Azis; Muhammad Kholis Hamdy (Faculty of Law, Universitas Pekalongan, 2024)
The transformation of globalization and the technological revolution have had a significant impact on the world of work, creating new challenges for college graduates who are expected to have not only academic knowledge, but also the ability to adapt quickly in the job market. This study aims to analyze the dynamics of career welfare and career adaptability to the perception of graduate career feasibility, with a focus on the UIN Jakarta Career Center. Using reflective and descriptive quantitative approaches, this study explores the influence of organizational identity on career adaptability and perception of career feasibility. Based on the data collected, the results of the study showed that career adaptability had a significant effect on the perception of career feasibility with values of β = 0.343, t = 2.861, and P = 0.004. In addition, career well-being was proven to affect career adaptability with β = 0.659, t = 31.969, and P < 0.001, as well as the perception of career feasibility with β = 0.583, t = 5.732, and P < 0.001. Organizational identity also had a significant effect on career adaptability (β = 0.352, t = 16.829, and P < 0.001) and perception of career feasibility (β = 0.747, t = 13.727, and P < 0.001). These findings highlight the importance of the Career Center's role in developing programs that improve career well-being, career adaptability, and improve the perception of graduates' career feasibility in facing the ever-changing world of work.